Leveraging Academia to Improve NGO Driven Intelligence - MacLeod, David (Journal of Conflict Studies, 2009)
ABSTRACT Criminals and irregular fighters target non-governmental organizations (NGOs) for a variety of political and economic reasons forcing some NGOs to increase their safety through NGO-driven intelligence. The analytic capability of NGO intelligence must be strengthened if NGOs are to survive in an increasingly dangerous operational environment. Academia, through remote access analysis, provides a non-intrusive approach to support NGO-driven intelligence.